1971
DOI: 10.1159/000459537
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Some Enzymes and Isoenzymes in Plasma Liver and Bile of Rats Treated with Carbon Tetrachloride

Abstract: Two different doses of carbon tetrachloride were administered orally to rats in order to produce acute liver injury. The release of enzymes into the blood stream, their levels in the liver tissue, and their elimination through the biliary tract were studied at various intervals after the drug administration. Cytosolic and mitochondrial enzymes were particularly increased in plasma ; the highest increases were observed with the higher dose of the drug. The plasma peak level of all the enzymes, except GLDH, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1972
1972
1990
1990

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A control group was given mineral oil only. In previous experiments this dose proved to be effective in producing liver cell necrosis within 48 h [8],…”
Section: Liver Necrosis Groupmentioning
confidence: 81%
“…A control group was given mineral oil only. In previous experiments this dose proved to be effective in producing liver cell necrosis within 48 h [8],…”
Section: Liver Necrosis Groupmentioning
confidence: 81%
“…Thus, whereas Koide and Oda [13], and Ideo et al [18] reported an increase in this enzyme at between 6 and 24 h in rats treated with CCI4, [15], and Zimmer man et al [16,17] found no variations in the activity of this enzyme. As far as we are con cerned, we did not find any significant vari ations in the levels of G6Pase throughout the entire study either.…”
Section: Discussionmentioning
confidence: 91%
“…Homogenates were rapidly frozen, thawed and submitted to ultrasonic treatment (3 times 20 s), then centrifuged for 20 min at 10000 g. The supernatant fluid was employed for the enzyme assay. This method was shown to be suitable for enzymatic estimations in liver homogenates (10).…”
Section: Methodsmentioning
confidence: 99%